2013
DOI: 10.1016/j.bbalip.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The polar lipids of Clostridium psychrophilum, an anaerobic psychrophile

Abstract: We have examined the polar lipids of Clostridium psychrophilum, a recently characterized psychrophilic Clostridium isolated from an Antarctic microbial mat. Lipids were extracted from cells grown near the optimal growth temperature (+5 °C) and at −5 °C, and analyzed by two-dimensional thin layer chromatography and liquid chromatography coupled with mass spectrometry. The major phospholipids of this species are: cardiolipin, phosphatidylethanolamine, and phosphatidylglycerol. Phosphatidylserine and lyso-phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Recent studies of clostridia have demonstrated that these are major components of the lipidome in C. difficile [3], Clostridiumtetani [8], Clostridium sporogenes , some strains of C. botulinum Group I that are related to C. sporogenes [6], Clostridium psychrophilum [4], and Clostridium acetobutylicum [5,29,30]. We note that three of the glycolipids common to Romboutsia , MHDAG, DHDAG and TriHDAG, were also found in C. difficile .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of clostridia have demonstrated that these are major components of the lipidome in C. difficile [3], Clostridiumtetani [8], Clostridium sporogenes , some strains of C. botulinum Group I that are related to C. sporogenes [6], Clostridium psychrophilum [4], and Clostridium acetobutylicum [5,29,30]. We note that three of the glycolipids common to Romboutsia , MHDAG, DHDAG and TriHDAG, were also found in C. difficile .…”
Section: Discussionmentioning
confidence: 99%
“…Since the review by Rezanka et al . plasmalogens have been documented in Clostridium botulinum , Groups I, II, III, and IV , Clostridium difficile [ ] , Clostridium sporogenes , Clostridium pasteurianum , and Clostridium psychrophilum . Di‐ and tetra‐alkyl ethers with polyisoprenoid chains are characteristic of Archaea .…”
Section: Comparison Of Fatty Aldehydes Derived From the Sn‐1 Alk‐1′‐ementioning
confidence: 99%
“…References: 1: Russell (1997), 2: Shivaji and Prakash (2010), 3: Zsiros et al (2000), 4: Oshima and Miyagawa (1974), 5: Chattopadhyay et al (1997), 6: Jagannadham et al (2000), 7: Guan et al (2013), 8: Wan et al (2016), 9: Nichols et al (2004), 10: Gibson et al (2005), 11: Sprott et al (1997), 12: Cario et al (2015), 13: De Rosa et al (1980), 14: Uda et al (2004), 15: Patel et al (1991), 16: Ray et al (1971), 17: Yokoyama et al (1996), 18: Damsté et al (2007), 19: Langworthy et al (1983), 20: Huber et al (1992), 21: Jahnke et al (2001), 22: Huber et al (1989), 23: Matsuno et al (2009), 24: De Rosa et al (1987), 25: Hafenbradl et al (1996), 26: Ulrih et al (2009), 27: Schleper et al (1995), 28: Kaneshiro and Clark (1995), 29: De Rosa et al (1974), 30: Wichlacz et al (1986), 31: Wakao et al (1994), 32: Matsubara et al (2002), 33: Mykytczuk et al (2010), 34: Weijers et al (2006), 35: Damste et al (2011), 36: Macalady et al (2004), 37: Uda et al (2001), 38: Clejan et al (1986), 39: Nogi and Kato (1999), 40: Knoblauch et al (1999), 41: Heinen et al (1970), 42: Li et al (1994), 43: Prowe and Antranikian (2001), 44: Clejan et al (1986), 45: Balk et al (2009), 46: Lee et al (2002), 47: Namwong et al (2007), 48: Feng et al (2005), 49: Castillo et al (2006), 50: Xu et al (2001), 51: Xu et al (1999), 52: Lanzotti et al (1989), 53: Tindall et al (1984), 54: Grant et al (1985), 55: Takai et al (2000), 56: Sako et al (1996), 57: Sprott et al (1991), 58: Hu et al (2008), 59: Bowers and Wiegel (2011), 60: Schleper et al (1995), 61: Feng et al (2005), 62: Xu et al (2001), 63: Lanzotti et al (1989) PUFA polyunsaturated fatty ...…”
Section: Introductionmentioning
confidence: 99%